Ectopic expression of embryonic stem cell and other developmental genes in cutaneous T-cell lymphoma - Litvinov, Ivan V (Oncoimmunology, 2014)
Cutaneous T-cell lymphoma (CTCL) is a potentially devastating malignancy. The pathogenesis of this cancer remains poorly elucidated. Previous studies focused on analysis of expression and function of known oncogenes and tumor suppressor genes. However, emerging reports highlight that it is also important to analyze the expression of genes that are ectopically expressed in CTCL (e.g., embryonic stem cell genes (ESC), cancer testis (CT) genes, etc.). Currently, it is not known whether ESC genes are expressed in CTCL. In the current work, we analyze by RT-PCR the expression of 26 ESC genes, many of which are known to regulate pluripotency and promote cancer stem cell-like phenotype, in a historic cohort of 60 patients from Boston and in a panel of 11 patient-derived CTCL cell lines and compare such expression to benign inflammatory dermatoses that often clinically mimic CTCL. Our findings document that many critical ESC genes including NANOG, SOX2, OCT4 (POU5F1) and their upstream and downstream signaling members are expressed in CTCL. Similarly, polycomb repressive complex 2 (PRC2) genes (i.e., EZH2, EED, and SUZ12) are also expressed in CTCL lesional skin. Furthermore, select ESC genes (OCT4, EED, TCF3, THAP11, CHD7, TIP60, TRIM28) are preferentially expressed in CTCL samples when compared to benign skin biopsies. Our work suggests that ESC genes are ectopically expressed together with CT genes, thymocyte development genes and B cell-specific genes and may be working in concert to promote tumorigenesis. Specifically, while ESC genes may be promoting cancer stem cell-like phenotype, CT genes may be contributing to aneuploidy and genomic instability by producing aberrant chromosomal translocations. Further analysis of ESC expression and function in this cancer will greatly enhance our fundamental understanding of CTCL and will help us identify novel therapeutic targets.